The Role of Demographic Variables in Traditional and Cyber Bullying in Jordanian Schools - Doaa Ameera; Fadwa Elashi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aimed to examine how bullying and cyberbullying may differ based on three demographic variables: Ethnicity, Grade Level, and Gender in Jordanian Schools. Methods: Bully-Victim and Cyberbullying measures were distributed to a sample consisted of Jordanian, Palestinian, Syrian students from third, fifth, seventh, and ninth grades, as well as students from other ethnicities. Results: Results showed that male fifth and seventh graders were bullied the most, and students from other ethnicities were victimized the most. They also showed that male students and fifth graders (from both genders) cyberbullied the most. Also, seventh graders have been cyber victimized the most. Conclusions: This study sought attention to some variables of which their effects on bullying weren't examined in the Arab region before, i.e., ethnicity and grade level. These results would play a big role in planning and executing intervention programs to prevent such behavior among the groups that were studied in this research.